2013
DOI: 10.1590/s0004-27302013000900001
|View full text |Cite
|
Sign up to set email alerts
|

The role of interferon induced with helicase C domain 1 (IFIH1) in the development of type 1 diabetes mellitus

Abstract: Type 1 diabetes mellitus (T1DM) is a chronic, progressive, autoimmune disease characterized by metabolic decompensation frequently leading to dehydration and ketoacidosis. Viral pathogens seem to play a major role in triggering the autoimmune destruction that leads to the development of T1DM. Among several viral strains investigated so far, enteroviruses have been consistently associated with T1DM in humans. One of the mediators of viral damage is the double-stranded RNA (dsRNA) generated during replication an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…In general, through recognition and attachment to pathogen‐associated molecular patterns (PAMPs) expressed on the surface or released by the pathogens, these effector cells result in the induction of the innate immune responses (Bouças, de Souza, Bauer, & Crispim, ).These procedures include: the production of chemokines which are chemo‐attractants for recruitment of immune cells to the site of injury and inflammation; secretion of inflammatory cytokines such as interleukin‐1 (IL‐1), IL‐6 and TNF‐α, and promoting the activation of other innate immune cells such as monocytes/macrophages and neutrophils in infectious conditions (Saito et al, ). PAMPs are recognized by a set of innate immunity receptors called pattern recognition receptors (PRRs) which consist of three major members including: Retinoic acid–inducible gene I (RIG‐I)‐like helicases (RLHs) typically capable of detecting dsRNA and triggering the innate antiviral responses (Bouças, Oliveira Fdos, Canani, & Crispim, ; Wilkins & Gale, ). NODlike receptors (NLRs) such as NOD1 and NOD2 that promote autophagy and inflammatory signaling to remove pathogens in host cells, and different members of the NLRP family that participate in the formation of inflammasome complexes (Liu, Rhebergen, & Eisenbarth, ). TLRs play a key role in the innate immune system through the production of Type I interferon (IFN‐I) and activation of mitogen‐activated protein kinase (MAPK), activator protein 1 (AP1), nuclear factor‐κB (NF‐kB) signaling pathways (Bouças et al, ).…”
Section: Innate Immunity and Pementioning
confidence: 99%
“…In general, through recognition and attachment to pathogen‐associated molecular patterns (PAMPs) expressed on the surface or released by the pathogens, these effector cells result in the induction of the innate immune responses (Bouças, de Souza, Bauer, & Crispim, ).These procedures include: the production of chemokines which are chemo‐attractants for recruitment of immune cells to the site of injury and inflammation; secretion of inflammatory cytokines such as interleukin‐1 (IL‐1), IL‐6 and TNF‐α, and promoting the activation of other innate immune cells such as monocytes/macrophages and neutrophils in infectious conditions (Saito et al, ). PAMPs are recognized by a set of innate immunity receptors called pattern recognition receptors (PRRs) which consist of three major members including: Retinoic acid–inducible gene I (RIG‐I)‐like helicases (RLHs) typically capable of detecting dsRNA and triggering the innate antiviral responses (Bouças, Oliveira Fdos, Canani, & Crispim, ; Wilkins & Gale, ). NODlike receptors (NLRs) such as NOD1 and NOD2 that promote autophagy and inflammatory signaling to remove pathogens in host cells, and different members of the NLRP family that participate in the formation of inflammasome complexes (Liu, Rhebergen, & Eisenbarth, ). TLRs play a key role in the innate immune system through the production of Type I interferon (IFN‐I) and activation of mitogen‐activated protein kinase (MAPK), activator protein 1 (AP1), nuclear factor‐κB (NF‐kB) signaling pathways (Bouças et al, ).…”
Section: Innate Immunity and Pementioning
confidence: 99%
“…IFIH1 and RIG-I are cytoplasmic PRRs that recognize different intracellular dsRNAs generated during viral replication. 8 After binding with dsRNA, IFIH1 and RIG-I will activate signaling pathways leading to NF-κB and interferon regulatory factor (IRF)-3 activation, ultimately driving the production of pro-inflammatory cytokines, chemokines, and IFN-I. Then, IFN-I binds to its receptor and activates the JAK/STAT pathway to drive the expression of IFN-regulated genes and the innate immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Then, IFN-I binds to its receptor and activates the JAK/STAT pathway to drive the expression of IFN-regulated genes and the innate immune response. 8,9,49 The role of IFIH1 and RIG-I in PE is still uncertain since only 1 study investigated these receptors in cases and controls 15 (Table 1). No study has evaluated the association between polymorphisms in IFIH1 or RIG-I genes and PE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The IFN induced with helicase C domain 1 (IFIH1) gene is located on chromosome 2q24.2, is induced by IFN type I, and encodes MDA5, an intracellular sensor of viral RNA [117]. It has been reported that the lower frequency of the T allele at the locus rs1990760 of IFIH1 in the African-American population might be associated with COVID-19 infection outcome due to decreased expression of IFN-β [118].…”
Section: Ifn Induced With Helicase C Domainmentioning
confidence: 99%